USABILITY WEBSITE EVALUATION FOR FRESH FOOD PRODUCT IN SME’S ONLINE BUSINESS WITH FUZZY AHP-TOPSIS INTEGRATION (ASEAN Engineering Journal, 2023)
Service providers are increasingly competing to give the highest quality services to satisfy website users with the increased competition. Therefore, small and medium-sized businesses (SMEs) should use technology in their product sales processes to become more competitive in the global market. This article will evaluate fresh food product e-commerce websites to see which one performs better in terms of usability. These parameters are investigated based on numerous research findings and the website attributes. To compare the outcomes, the evaluation was carried out using two alternative methods: fuzzy AHP and fuzzy TOPSIS. Fuzzy AHP results and analysis were used to determine the weights of the main and sub-factors, while Fuzzy TOPSIS was used to determine the ranking of alternatives. A Triangular Fuzzy Number (TFN) deals with poor assessments in biased judgments. The result from this study shows that the best website usability is website-1 because it closely follows crucial factors compared to the other two websites. The Website-3 comes in second, followed by the Website-2. Website-1 had the highest relative closeness score (0.5333), indicating that Website-1 has the best usability level among the three websites examined in this study. With a relative closeness of 0.5143, Website-3 came in second. Website-2 received the lowest score (0.5012), indicating that it has the least application of the critical success characteristics required for a fresh food product e-commerce website with the best usability level.